Slip casting and pressureless sintering of Ti3AlC2 - Yimin Gong; Wubian Tian; Peigen Zhang; Jian Chen; Yamei Zhang; Zhengming Sun (Journal of Advanced Ceramics, 2019)
Abstract Slip casting and subsequent pressureless sintering (PLS) allow the preparation of complex-shaped and large-sized Ti3AlC2 components for many potential applications. The behaviors of the suspensions, green compacts, and sintered samples of Ti3AlC2 were studied in this paper. The optimized condition of 1 wt% of arabic gum as dispersant at pH = 10 results in a Ti3AlC2 suspension for slip casting Ti3AlC2 green compacts without macro defects or cracks. The sintering temperature and A14C3 embedding powder are found to dominate the properties of the sintered Ti3AlC2 samples. The Ti3AlC2 sample sintered at 1450 °C for 1.5 h with A14C3 embedding powder reaches the best properties, namely 95.3% relative density, hardness of 4.18 GPa, thermal conductivity of 29.11 W·m−1K−1, and electrical resistivity of 0.39 μΩ·m. The findings in this work may pave the way for the application of MAX phases with large size and complex shape